Emperor and nation in Japan : - Earl, David Magarey (Greenwood Press, 1981)
This study attempts to explain the development of Tokugawa-period political attitudes, as shown in the writings of the major thinkers of the time and as exemplified in the life of a nineteenth-century samurai. Emphasis is placed on attitudes toward emperor and nation, a subject that also involved the role of the Bakufu, or Tokugawa shogunate government.